The impact of digitization in Spanish scholarly publishers - Magadán Díaz, Marta; Rivas García, Jesús Israel (LIBER Quarterly, 2019)
This paper analyzes the impact of digitization on the Spanish scholarly publishing sector. Scholarly publishers are those publishing mainly books of interest to the scientific, academic and/or university community or that deal with scientific disciplines. In Spain, there are currently 673 publishers whose books are classified in disciplines such as Science, Technology, Medicine, Humanities and Social Sciences. Currently, this figure of scholarly publishers equals approximately 20% of all Spanish publishers. The present study has two main goals: a) to determine the degree to which digitization is affecting the existing business models in Spanish scholarly publishers and b) to identify the emergence of new business models in the Spanish scholarly publishing sector. To carry out this research, an empirical analysis is conducted by means of surveys sent to a sample extracted from the population of scholarly Spanish publishers, following the criterion of stratified random sampling.
Keywords: digitization; Scholarly publishers; ePublishing; Spain; Scopus